Planned Residential Suburbs after the Second World War: Refining the Model - Poitras, Claire (Montreal: The History of A North American City, 2018)
Keywords: Banlieue; Brossard; Candiac; Lorraine

Les banlieues résidentielles planifiées dans la région de Montréal après la Seconde Guerre mondiale. Un modèle en redéfinition? - Poitras, Claire (Histoire de Montréal et de sa région, 2012)
Keywords: Banlieue; Brossard; Candiac; Lorraine

Une famille noble en Nouvelle-France: les d'Ailleboust - Gadoury, Lorraine (Université de Montréal, 1982)
Keywords: Ailleboust, d' (famille); Famille

Marguerite D'Youville - Létourneau, Lorraine (Célébrités canadiennes, 1991)
Keywords: Communautés religieuses; Dufrost de Lajemmerais, Marie-Marguerite (Youville, Marguerite d'); Soeurs Grises

La noblesse de Nouvelle-France. Familles et alliances - Gadoury, Lorraine (Cahiers du Québec, 1992)
Keywords: Famille; Noblesse

Comportements démographiques et alliances de la noblesse de Nouvelle-France - Gadoury, Lorraine (Université de Montréal, 1988)
Keywords: Mariage; Noblesse

Trois interventions du clergé dans l'histoire du théâtre à Montréal: 1789-90, 1859 et 1872-74 - Camerlain, Lorraine (Université de Montréal, 1979)
Keywords: Théâtre

Montréal: l’archipel suspendu - Guay, Lorraine (Continuité, 2000)
Keywords: Voie maritime; Île Jésus; Île Notre-Dame; Île Sainte-Hélène

Jeanne Mance - Létourneau, Lorraine (Célébrités canadiennes, 1990)
Keywords: Hôpitaux; Hôtel-Dieu; Mance, Jeanne

Jeanne LeBer - Létourneau, Lorraine (Célébrités canadiennes, 1990)
Keywords: Le Ber, Jeanne

ROBERTSON, MARGARET MURRAY - McMullen, Lorraine (Dictionnaire biographique du Canada, 1990)

EATON, EDITH MAUD - McMullen, Lorraine (Dictionnaire biographique du Canada, 1998)

Le voyage virtuel. Les consommatrices, le monde de l'étranger et Eaton à Montréal, 1880-1980 - O'Donnell, Lorraine (Revue d'histoire de l'Amérique française, 2005)
Keywords: Eaton; Femmes; Magasins

Visualising the History of Women at Eaton's, 1869 to 1976 - O'Donnell, Lorraine Frances (Université McGill, 2002)
This thesis examines the place of female customers and employees at the T. Eaton Company of Canada between 1869 and 1976. The central argument is that the word "witness" conveys well the nature of their place in this, one of the most important retail firms in Canadian history. Women were witnesses for the Eaton's and its development. They attested to and consolidated the company by collectively supporting it in huge numbers, whether as customers or personnel. Women were also key eyewitnesses of Eaton's, of its merchandise and marketing, its stores and catalogues. As the word "witness" suggests, visuality was central to women's central place. Women bought into the Eaton's buying and selling strategies that privileged appearances, and the company assumed and fostered this visually-centered role, helping to construct it and encouraging women to adopt it. The Introduction to the thesis reviews the substantial literature on the company's history. The main body of the thesis is divided in two. Part I examines the company's foreign activities and the role of women therein. Following a description of the firm's foreign buying system is an examination of three of its main regions: Japan, Europe and the U.S.A. The closer the region was to Canada, the more familiar it was to Eaton's, the more female Eatonians were employed there, and the more these women were able carve out a niche for themselves as expert witnesses like fashion buyers or fashion reporters. Part II discusses the place of women in the company's activities within Canada. First, it outlines the history of and tensions between the company's two main retail sites: stores and catalogues. While run by men, these sites were "spectacles of women" including salesclerks, mannequins and customers. Examples considered in depth are Eaton's catalogue covers and store displays for foreign goods and places. They privileged female imagery, a strategy meant to add value both to the merchandise and the (incomplet)
Keywords: Eaton; Femmes; Magasins

Marguerite Bourgeoys - Létourneau, Lorraine (Célébrités canadiennes, 1990)
Keywords: Bourgeoys, Marguerite; Communautés religieuses; Congrégation de Notre-Dame

La présence des communautés religieuses de femmes dans l’espace québécois, de 1900 à 1970 - Laurin, Nicole; Duchesne, Lorraine (Études d'histoire religieuse, 1993)
Keywords: Communautés religieuses; Femmes

Profil de quelques bourgeois de Montréal, 1820-1825 - Gadoury, Lorraine; Leclerc, Jean-François (Cahiers d'histoire, 1985)
Keywords: Bourgeoisie

Les Bâtisseuses de la Cité - Tardy, Évelyne; Descarries, Francine; Archambault, Lorraine; Kurtzman, Lyne; Piché, Lucie (Association canadienne-française pour l'avancement des sciences, 1993)
Keywords: Femmes

Les services du Traveller’s Aid pour l’accueil aux immigrants: identités de genre et de religion au Québec au XXe siècle - Cohen, Yolande (L'État canadien et la diversité culturelle et religieuse, 1800-1914, 2009)
Keywords: Femmes; Young Women's Christian Association (YWCA)

Marie Morin: vivante mémoire des amazones de Ville-Marie - Théry, Chantal (Les Bâtisseuses de la Cité, 1993)
Keywords: Morin, Marie

Les femmes et le vote au Bas-Canada, 1791-1849 - Picard, Nathalie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Élections

L'animation de la paroisse montréalaise: un aspect méconnu du travail des femmes dans la ville. Les années 1950 - Lafortune, Agathe (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Travail

Journaliste au masculin: Éva Circé-Côté (1871-1949) - Lévesque, Andrée (Les Bâtisseuses de la Cité, 1993)
Keywords: Circé-Côté, Éva; Journalistes

Le formalisme au féminin. Rita Letendre. Peintre et muraliste - Carani, Marie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Peinture

Les femmes "peintres de la cité" - Trépanier, Esther (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Peinture

La consultation publique à Montréal: un affaire de femmes? - Cloutier, Céline (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Accession des femmes à l'enseignement supérieur et origines d'une pratique architecturale féminine - Tremblay, Katia (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Les maîtresses d'écoles indépendantes: une contribution essentielle à l'éducation de la jeunesse montréalaise du premier tiers du XIXe siècle - Dufour, Andrée (Les bâtisseuses de la Cité, 1993)
Keywords: Enseignants; Femmes

Le leadership féminin dans les associations privées de charité protestantes au XIXe siècle à Montréal - Harvey, Janice (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Protestants

Projets et pratiques de femmes architectes - Vescei, Éva (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Elles disent leur dépaysement et bâtissent leur repaysement - Lequin, Lucie (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

La communication musicale à travers des femmes que j'ai connues - Kendergi, Maryvonne (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Musique

La ville: un milieu d'engagement politique privilégié pour les femmes: le cas de Montréal - Maillé, Chantal (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

La fin d'un univers féminin: l'Enquête Caron et la prostitution, 1945-1965 - Lacasse, Danielle (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Prostitution

La sécurité des femmes dans la ville - Cousineau, Léa (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Marguerite Lacorne, conseillère de Jacques Viger - Robillard, Denise (Les Bâtisseuses de la Cité, 1993)
Keywords: Lacorne (famille); Maires; Viger, Jacques

Le verre-écran de Marcelle Ferron, station de métro de Champ de Mars: la querelle des anciens et des modernes - Couture, Francine (Les Bâtisseuses de la Cité, 1993)
Keywords: Champ-de-Mars; Transport en commun; Vitraux

Y a-t-il une musique virile? - Panneton, Isabelle (Les Bâtisseuses de la Cité, 1993)
Keywords: Musique

L'importance des femmes dans la vie musicale montréalaise entre les deux guerres: mythe ou réalité? - Paul, Hélène (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Musicien; Musique

Les religieuses enseignantes auraient-elles fait la Révolution tranquille si on leur en avait laissé le temps? - Hamel, Thérèse (Les Bâtisseuses de la Cité, 1993)
Keywords: Communautés religieuses; Enseignants

Les femmes et la prise de décision au niveau municipal - Pelletier, Lyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Conseillers municipaux; Femmes

Les infirmières de la Métropolitaine au service des Montréalaises - Baillargeon, Denyse (Les Bâtisseuses de la Cité, 1993)
Keywords: Assurance; Femmes; Infirmières

Les congrégations féminines et la fondation des écoles normales de filles à Montréal - Malouin, Marie-Paule (Les Bâtisseuses de la Cité, 1993)
Keywords: Communautés religieuses; Écoles normales

La musique composée au féminin - Martin-Kostajnsek, Sylvaine (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes; Musicien; Musique

Existe-t-il une musique dite féministe? - Lefebvre, Marie-Thérèse (Les Bâtisseuses de la Cité, 1993)
Keywords: Féminisme; Musique

Elles, dans la ville - Saint-Martin, Lori (Les Bâtisseuses de la Cité, 1993)
Keywords: Femmes

Madeleine de La Peltrie et la fondation de Montréal - Deroy-Pineau, Françoise (Les Bâtisseuses de la Cité, 1993)

Une passion: la science. Portraits de pionniers québécois - Chabot, Claire (Les Éditions Multimondes Inc., 1990)
Keywords: Boulet, L.; Dansereau, P.; Frappier, Armand; Gauvin, W. H.; Gouin-Décarie, T.; Lorrain, P.; Marie-Victorin, Frère; Milner, B; Penfield, Wilder; Rousseau, J.; Selye, H.; Séguin, Fernand